The role of Gluconate shunt in the immunity of Drosophila melanogaster - Dolejšková, Tereza (Jihočeská univerzita, 2023)
The Pentose phosphate pathway is a basic sugar metabolism pathway present in all living organisms. It has been thoroughly studied due to its immense importance. However, its alternative entry, the Gluconate shunt, has only been characterized in plants, algae, and some microorganisms. Here we study the potential existence of Gluconate shunt in Drosophila immune cells and its possible interaction with the Pentose phosphate pathway.
The role of Gluconate shunt in the immunity of Drosophila melanogaster
Keywords: Pentose phosphate pathway; 13C metabolomics; gluconate; Drosophila melanogaster; immunity; Pentose phosphate pathway; 13C metabolomics; gluconate; Drosophila melanogaster; immunity